Thermodynamic insights into selenium oxyanion removal from synthetic flue gas desulfurization wastewater with temperature-swing solvent extraction - Meissner, Michael S.; Nguyen, Vy H. T.; Bousrih, Imen; Le, Van T. C.; Frickenstein, Alex; Le, Giang V.; Bui, Ngoc T. (Frontiers in Chemistry, 2023)
Temperature-swing solvent extraction (TSSE) is a cost-effective, simple, versatile, and industry-ready technology platform capable of desalinating hypersaline brines toward zero liquid discharge. In this work, we demonstrate the potential of TSSE in the effective removal of selenium oxyanions and traces of mercury with the coexistence of high contents of chloride and sulfate often encountered in flue gas desulfurization wastewater streams. We compare the rejection performance of the two common solvents broadly used for TSSE, decanoic acid (DA) and diisopropylamine (DPA), and correlate those with the solvent physicochemical properties (e.g., dielectric constant, polarity, molecular bulkiness, and hydrophobicity) and ionic properties (e.g., hydrated radii and H-bonding). The results show that TSSE can remove >99.5% of selenium oxyanions and 96%–99.6% of mercury traces coexisting with sulfate (at a sixfold Se concentration) and chloride (at a 400-fold Se concentration) in a synthetic wastewater stream. Compared to diisopropylamine, decanoic acid is more effective in rejecting ions for all cases, ranging from a simple binary system to more complex multicomponent systems with highly varied ionic concentrations. Furthermore, the H-bonding interaction with water and the hydrated radii of the oxyanions (i.e., selenate vs. selenite) along with the hindrance effects caused by the molecular bulkiness and hydrophobicity (or lipophilicity) of the solvents play important roles in the favorable rejection of TSSE. This study shows that TSSE might provide a technological solution with a high deionization potential for the industry in complying with the Environmental Protection Agency regulations for discharge streams from coal-fired power facilities.